World development report 1986. - World Bank. (New York : Oxford University Press, 1986)
The report examines trade and pricing policies in world agriculture. Concern about these policies has arisen not only in the many developing countries that depend heavily on agriculture, but also in the industrial market economies whose farm support programs have become very expensive
Bibliography: p. 256.
osc 26/03/2019
Loans
Keywords: Economic development; Developing countries